2020
DOI: 10.1101/2020.09.21.305441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A natural mutation between SARS-CoV-2 and SARS-CoV determines neutralization by a cross-reactive antibody

Abstract: Epitopes that are conserved among SARS-like coronaviruses are attractive targets for design of cross-reactive vaccines and therapeutics. CR3022 is a SARS-CoV neutralizing antibody to a highly conserved epitope on the receptor binding domain (RBD) on the spike protein that can cross-react with SARS-CoV-2, but with lower affinity. Using x-ray crystallography, mutagenesis, and binding experiments, we illustrate that of four amino acid differences in the CR3022 epitope between SARS-CoV-2 and SARS-CoV, a single mut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…These observations are similar to some broadly neutralizing influenza antibodies to the hemagglutinin (HA) receptor binding site, where bivalent binding can increase avidity and neutralization breadth (Ekiert et al, 2012;Lee et al, 2012). Nevertheless, we have shown recently that the CR3022 Fab and IgG have similar neutralization potency as a SARS-CoV-2 variant with enhanced binding affinity for CR3022 (Wu et al, 2020a), suggesting that an avidity effect is not universally observed for all RBD-targeting antibodies, especially to this particular epitope, which is targeted by CR3022 and COVA1-16.…”
Section: The Neutralization Activity Of Cova1-16 Is Promoted By Igg Bsupporting
confidence: 72%
“…These observations are similar to some broadly neutralizing influenza antibodies to the hemagglutinin (HA) receptor binding site, where bivalent binding can increase avidity and neutralization breadth (Ekiert et al, 2012;Lee et al, 2012). Nevertheless, we have shown recently that the CR3022 Fab and IgG have similar neutralization potency as a SARS-CoV-2 variant with enhanced binding affinity for CR3022 (Wu et al, 2020a), suggesting that an avidity effect is not universally observed for all RBD-targeting antibodies, especially to this particular epitope, which is targeted by CR3022 and COVA1-16.…”
Section: The Neutralization Activity Of Cova1-16 Is Promoted By Igg Bsupporting
confidence: 72%
“…Despite the direct overlap of the epitopes with residues binding to the human ACE-2 receptor and higher binding a nity than SARS-CoV-2 S protein RBD and hACE-2, these three mutants display average interaction energies for the wild type CR3022 and the lead L-K45S. Wu et al demonstrate that the P384 residue is responsible for determining the a nity between the cross-reactive antibody and SARS-CoV-2 RBD [26]. In SARS-CoV, this position consists of alanine instead of proline and is the reason behind successful neutralization by CR3022, unlike the case with binding of the same antibody with SARS-CoV-2 RBD.…”
Section: K45w K45m and Q48w Mutantsmentioning
confidence: 99%
“…The affinity of the cross reactive SARS-CoV-1 antibody, CR3022, whose epitope is located in the conserved area just upstream of the JS7 site, 28 was greatly reduced by the single amino acid change, P to A found in the SARS-CoV-2 protein. 29 Further, while all 9 COVID-19 patients in this study had antibodies that recognize the RBD of SARS-CoV-2, one patient with mild illness did not recognize the whole S protein of SARS-CoV-1 (protein 2), despite the 80% overall sequence identity (Table 1, S1). Further, some variants in this area, which also arose as escape mutants of monoclonal antibodies 40 , can render the virus insensitive to neutralization by convalescent sera 41 .…”
Section: See Supplementarymentioning
confidence: 72%
“…Many assays for determining prior COVID-19 infection are based on detecting antibodies in sera to recombinant versions of the surface (S) protein, which was previously identified as the binding site for neutralizing antibodies produced in response to SARS-CoV-1. At least one SARS-CoV-1 neutralizing monoclonal antibody 28,29 also binds with less affinity to the S protein SARS-CoV-2 30 , which varies by about 20% throughout its length ( Fig. S1).…”
Section: Introductionmentioning
confidence: 99%